Challenges facing real estate development start-ups in the inner City of Johannesburg in accessing finance from commercial banks: A South African context - Qwabe, Leonard (My University, 2018)
Access to finance from commercial banks is a major barrier for Small and medium Business Enterprises (SMEs).The problem persists because of the stringent requirements the commercial banks put on the SMEs. The research attempted to determine whether or not Venture Capital or the Trust for Urban Housing Finance (TUHF) can be alternative sources of finance for inner city residential real estate development start-ups instead of commercial banks. The research evaluated some of the key reasons that the commercial banks put forth for rejecting SMEs loan application. The study is descriptive in nature, the data was collected using both an electronic survey and a printed questionnaire measuring the primary data sourced from the respondents, who are practising in the inner city property development space. The results are contrary to the expectation of the researcher and the literature reviewed. In the literature, track-record and collateral plays a major role in start-up inner city residential real estate developers lack of access to finance from commercial banks. The findings, however, show that track-record and collateral have weak relationship with access to finance from commercial banks for the start-up developers. Furthermore, the TUHF as an alternative source of finance had no results because the start-up real estate developers from the TUHF did not participate in large numbers. Venture capital as an alternative source of finance has a weak relationship with access to finance from commercial banks. Hence, venture capital cannot be seen as an alternative source of finance from commercial banks.
Research Report submitted to the Faculty of Engineering and the Built Environment, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Science in Building (Property Development and Management),2018